(3TQM geRjI GHf PcQi GdJi CfTCgG aj eOM GdfHi Udi Gddg Ydjg hSdes - (3CHh YHO Gddg eMeO Hf YHO GdQMef Hf RcQjs; (3GHf RcQj , CHh YHO Gddg eMeO Hf YHO GdQMef Hf RcQj,J (B1144 (3g` s ((3eMeO Hf eMeO Hf eUWai GdHbGdi GdMSfi s)
(3ChdgG (B:s
(3hHYO , aEfG cfG hVYfG ai eOMg Udi Gddg Ydjg hSde bUjOI geRjI hdeGJ CWdY YYdi GdbUjOI GdePchQI HYV GdENhGf WdHhG efi Cf CbjO YdjgG TQMkG s
(3BNQgG (B:s
(3GdLfGS GddGMb fMh (B: (3Pdce HeG cfJe JaQMhf ai GdCQV HZjQ GdMb hHeG cfJe JeQMhf s
(3hgj geRjI ai eOM GdfHi Udi Gddg Ydjg hSdes
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs